CHANGES AND CHALLENGES IN THE DEVELOPMENT OF LIGHT AND FOOD INDUSTRIES IN THE SOUTHERN REGIONS OF UZBEKISTAN - Худойқулов У.К. (TARIXIY TADQIQOTLAR, 2026)
This article describes in detail the relationship of workers of industrial enterprises to housing in the 70s-80s of the 20th century. Also, practical works were carried out on the basis of the state plan in order to improve the construction of housing, administrative-household, and service buildings, to create new construction projects, and to involve them in production. However, housing construction organizations commissioned due to the poor quality of newly built residential buildings, lack of internal equipment, water and gas supply failure, nonconformity of reinforced concrete buildings to local conditions were analyzed as not adapted to modern needs.